CTF/MWCNT hybrid multi-functional separator as high-efficiency polysulfide tamer for high-performance Li–S battery. (20th January 2021) - Shi, Qing Xuan; Chang, Chen; Pei, Hui Jie; Guan, Xin; Yin, Liang Liang; Xie, Xiao Lin; Ye, Yun Sheng
Abstract: The lithium–sulfur (Li–S) battery holds great promising for the next-generation energy storage system due to its high theoretical specific capacity and energy density. However, the poor conductivity of sulfur species and the "shuttle effect" of polysulfides (PSs) severely limit the practical application of Li–S battery. Here, a large-scaled covalent triazine framework/multiwall carbon nanotube (CTF/MWCNT) hybrid used as a multi-functional separator modifier combining strong PSs-anchor ability of CTF with high electrical conductivity of MWCNT was proposed. The ordered porous structure and large specific surface area of CTF make it good physical trap ability for PSs shuttle, and the abundant pyridinic nitrogen groups of CTF render it effectively adsorb PSs by chemical sorption, while the high electrical conductivity of MWCNT can facilitate electron transfer. As it turns out that the multi-functional separator applied in Li–S battery shows significant enhancements in the utilization of sulfur, specific capacity, Columbic efficiency, rate capability (982 mAh g −1 at 2 C) and cycling stability (0.045% specific capacity loss per cycle at 1 C along 1000 cycles) as well as suppression of self-discharge and Li dendrite growth. Furthermore, it is practicable to incorporate the slurry cast multi-functional layer onto the commercial separator, which provides ideas for constructing advanced multi-functional separators for commercially viable Li–S battery.